2020
DOI: 10.3390/nano10061120
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Nano/Micro-Structured Degradable Polymeric Meshes for Pelvic Floor Reconstruction

Abstract: Pelvic organ prolapse (POP) is a hidden women’s health disorder that impacts 1 in 4 women across all age groups. Surgical intervention has been the only treatment option, often involving non-degradable meshes, with variable results. However, recent reports have highlighted the adverse effects of meshes in the long term, which involve unacceptable rates of erosion, chronic infection and severe pain related to mesh shrinkage. Therefore, there is an urgent unmet need to fabricate of new class of biocompatible mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 166 publications
(287 reference statements)
0
22
0
Order By: Relevance
“…Recently, several groups have shown that electrospun constructs fabricated with degradable polymers have significant potential in POP treatment using small and large animal models [ [12] , [13] , [14] , [15] , [16] ]. We have previously shown that choice of polymer and surface topography largely influences the triggered in vivo immune response [ 17 ]. These features, and physical and mechanical properties such as fibrous architecture and large pore size (one mm diam), determine cellular attachment and infiltration, cytokine release and ectopic recruitment of tissue forming cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several groups have shown that electrospun constructs fabricated with degradable polymers have significant potential in POP treatment using small and large animal models [ [12] , [13] , [14] , [15] , [16] ]. We have previously shown that choice of polymer and surface topography largely influences the triggered in vivo immune response [ 17 ]. These features, and physical and mechanical properties such as fibrous architecture and large pore size (one mm diam), determine cellular attachment and infiltration, cytokine release and ectopic recruitment of tissue forming cells.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is a versatile technique used to fabricate fibers that has recently gained attention in urogynecological applications [ 15 , 17 , 23 ]. Electrospinning provides an adaptable path for the construction of nanofibers and microfibers with defined fiber morphology, dimensions and orientation, which present the multiple benefits of a high surface-to-volume ratio and twisting to generate yarns, which is conducive to delivering reproducible textiles [ 24 ] as demonstrated here.…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal birth results in stress to the vaginal wall and surrounding ligamentous, fascial, and muscular structures, beyond their critical stretch limit, resulting in tissue damage through non-elastic deformation [ 19 ]. During labour, pressure from strong uterine contractions and the transiting foetal head are directed to the LAM muscle, particularly the medial portion of the pubococcygeus.…”
Section: Pelvic Organ Prolapsementioning
confidence: 99%
“…These emerging biomimetic electrospun meshes produce an ECM-like topography that mimic the ECM of vaginal tissue of women with POP at the nanoscale [ 73 ]. Nanostructured meshes also provide a larger surface area for the delivery of eMSC and other adsorbing proteins and growth factors [ 19 , 73 ]. Poly-L-lactide-co-ε-caprolactone (PLCL) is a biocompatible, elastic, and flexible polymer investigated by several groups for novel tissue engineering applications, as its elastic modulus is well matched to the nanoarchitecture of vaginal tissue [ 81 ].…”
Section: Engineering Novel Meshes With Emscmentioning
confidence: 99%
See 1 more Smart Citation